Spiritualitas Relasional: Antara Dosa Dan Masa Lampau - Debi Silvia Dinata; Devi Lestary; Tirza Tanzania; Sarmauli Sarmauli (Tri Tunggal: Jurnal Pendidikan Kristen dan Katolik, 2024)
Sin and the past are two crucial concepts in Christian spirituality that significantly impact an individual’s spiritual life. Sin is defined as a violation of God’s law, resulting in damage and conflict. Meanwhile, the past encompasses the totality of past events and experiences, including sins committed, which can carry emotional and spiritual burdens. Sin separates humans from God, but God forgives through the sacrifice of Jesus on the cross. Handling sin and the past involves confession of sins, repentance, acceptance of forgiveness, learning from the past, and transformation through Christ’s love. Biblical teachings provide guidance in facing sin and the past, encouraging self-forgiveness and forgiveness of others. In daily life, this is applied through worship, spiritual growth, Christian community, meditation, service, and self-awareness. By following these principles, Christians can overcome the challenges posed by sin and the past, attain peace, and experience spiritual growth and restoration of their relationship with God